2016
DOI: 10.1080/02813432.2016.1207145
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ socioeconomic factors related to high antibiotic prescribing in primary health care among children aged 0–6 years in the Capital Region of Denmark

Abstract: ObjectiveTo investigate the distribution of antibiotic prescriptions in primary health care among children aged 0–6 years and its association with socioeconomic factors.DesignA cross-sectional study describing antibiotic prescriptions and socioeconomic factors, using different population-based registers from Statistics Denmark.SettingAntibiotic prescriptions in 2012 from primary health care in the Capital Region of Denmark.SubjectsThe population of children aged 0–6 years (n = 139,398) in the Capital Region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 23 publications
3
37
0
2
Order By: Relevance
“…Families, especially mothers, attach great importance to past experience. Parents who have previously observed their child recover from a fever by using antibiotics tend to want to use antibiotics for every similar episode later and can be insistent about this toward physicians [56] . Similarly, parents who claim their febrile child is not improving sufficiently and demand re-evaluation can be more insistent about the prescription of antibiotics by physicians [57] .…”
Section: Pressure From Families To Use Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Families, especially mothers, attach great importance to past experience. Parents who have previously observed their child recover from a fever by using antibiotics tend to want to use antibiotics for every similar episode later and can be insistent about this toward physicians [56] . Similarly, parents who claim their febrile child is not improving sufficiently and demand re-evaluation can be more insistent about the prescription of antibiotics by physicians [57] .…”
Section: Pressure From Families To Use Antibioticsmentioning
confidence: 99%
“…It was reported that if maternal pressure to get antibiotics could be reduced, the amount of antibiotics prescribed to children could be reduced by nearly half [56] . In a study in which families were asked where they got information about antibiotics, the most common source was physicians, followed by television and relatives [53] .…”
Section: Pressure From Families To Use Antibioticsmentioning
confidence: 99%
“…Antibiotic exposure is often higher in disadvantaged populations [260,261,262]. The microbes carried by mammals are also a product of the ecosystems in which they reside [263,264,265,266]; given that the Earth is home to upward of 1 trillion microbial species [267], human contact with many of these microbes in natural environments (the ecosystem in which we once spent the majority of our time) may have evolutionary-rooted, health-protective properties.…”
Section: Hygiene Hypothesis Dysbiotic Driftmentioning
confidence: 99%
“…Moreover, in the relationship between physician empathy, humility and good medical outcomes, perception is likely a reality [345,346]. Given that inappropriate antibiotic prescriptions remain alarmingly high [347], it is worth noting that in the visualized neighborhood, one where primary care demands are typically strong, consultations shorter and provider stress is higher [348], a physician visit in our neighborhood is more likely to conclude with an antibiotic prescription [260,261,262]. Clearly, the “ecology“ of the patient visit and its direct and indirect effects on the microbiome requires further study.…”
Section: Behavioral Reinforcementmentioning
confidence: 99%
“…More evidence on the role of social determinants in patient well-being is being uncovered, for example, that parents’ socioeconomic factors are related to higher antibiotic prescribing for children. [6] However, despite the fact that western countries are spending more money on their health system, inequality still exists and is even increasing. People on low incomes and immigrants are accepting different health care service than those who have higher incomes and less social problems.…”
mentioning
confidence: 99%